Transversal analysis of predictors, mediators and related effects of heavy work investment - Claudiu George Bocean; Anca Antoaneta Varzaru; Anca Bandoi; Catalina Soriana Sitnikov (Amfiteatru Economic Journal, 2020)
In recent years, the significant and intensive change of working conditions necessitates employees to modify their work patterns to increase the number of working hours and work intensity by improving the efforts, which leads to the occurrence of the heavy work investment (HWI) phenomenon. Analyzing the models of HWI we can distinguish two types: workaholism (WH), considered being the negative form of the HWI, and working engagement (WE), considered to be the positive form of the HWI. This paper proposes a multidimensional model of HWI that is built on four main elements: HWI (with its two types: WH and WE), potential predictors, work outcomes and mediating factors between HWI and work outcomes. The model is empirically tested on a sample of 298 Romanian employees, using correlational study, confirmatory factorial analysis, and artificial neural networks analysis established between model variables. The results of the research are explained and discussed, recommendations are issued for the improvement of organizational practices and new research directions are proposed.
Keywords: O15; 330; HWI; WH; WE; work addiction; job satisfaction